Monocyte Induction of E-Selectin-Mediated Endothelial Activation Releases VE-Cadherin Junctions to Promote Tumor Cell Extravasation in the Metastasis Cascade - Häuselmann, Irina; Roblek, Marko; Protsyuk, Darya; Huck, Volker; Knopfova, Lucia; Grässle, Sandra; Bauer, Alexander T; Schneider, Stefan W; Borsig, Lubor (Cancer research, 2016)
Tumor cells interact with blood constituents and these interactions promote metastasis. Selectins are vascular receptors facilitating interactions of tumor cells with platelets, leukocytes, and endothelium, but the role of endothelial E-selectin remains unclear. Here we show that E-selectin is a major receptor for monocyte recruitment to tumor cell-activated endothelium. Experimental and spontaneous lung metastasis using murine tumor cells, without E-selectin ligands, were attenuated in E-selectin-deficient mice. Tumor cell-derived CCL2 promoted endothelial activation, resulting in enhanced endothelial E-selectin expression. The recruitment of inflammatory monocytes to metastasizing tumor cells was dependent on the local endothelial activation and the presence of E-selectin. Monocytes promoted transendothelial migration of tumor cells through the induction of E-selectin-dependent endothelial retractions and a subsequent modulation of tight junctions through dephosphorylation of VE-cadherin. Thus, endothelial E-selectin shapes the tumor microenvironment through the recruitment, adhesion, and activation of monocytes that facilitate tumor cell extravasation and thereby metastasis. These findings provide evidence that endothelial E-selectin is a novel factor contributing to endothelial retraction required for efficient lung metastasis. Cancer Res; 76(18); 5302-12. ©2016 AACR.
Keywords: imunoprecipitace; Antigens, CD; Tight Junctions; imunoblotting; CD antigeny; mutantní kmeny myší; Endothelium, Vascular; cévní endotel; Cadherins; Transendothelial and Transepithelial Migration; Neoplasm Invasiveness; zvířata; myši; Mice; Endothelial Cells; E-selektin; Flow Cytometry; polymerázová řetězová reakce; těsný spoj; kadheriny; Polymerase Chain Reaction; nádorové buněčné linie; endoteliální buňky; transendoteliální a transepiteliální migrace; Immunoblotting; Monocytes; průtoková cytometrie; invazivní růst nádoru; Mice, Mutant Strains; monocyty; Animals; Cell Line, Tumor; Immunoprecipitation; Disease Models, Animal; E-Selectin; modely nemocí na zvířatech